Disturbances of sleep and circadian rhythms: novel risk factors for obesity. Issue 5 (October 2016) - Broussard, Josiane L.; Van Cauter, Eve
Abstract : Purpose of review: The purpose of this review is to summarize recent developments linking disturbances of sleep and circadian rhythms to an increased risk for obesity, and to review novel research on potential countermeasures. Recent findings: Effective treatments for obesity are limited, with long-term adherence to lifestyle changes proving difficult to maintain. Identifying new preventive strategies based on modifiable risk factors is therefore imperative in the fight against obesity. Disturbances of sleep and circadian rhythms have an adverse impact on food choices, hunger and appetite, and have lifelong deleterious metabolic consequences when they occur during childhood and early adulthood. The upregulation of the endocannabinoid system and abnormalities in the temporal distribution of caloric intake were recently implicated in the link between sleep loss and obesity risk. In addition, alterations in circadian variation in the composition and functionality of the gut microbiome have been identified as potential contributors to metabolic dysfunction during jet lag and shift work. Insufficient sleep and circadian misalignment are thus new modifiable risk factors for obesity. Emerging evidence suggests that novel countermeasures, such as manipulations of the timing of food intake, may be effective strategies in the prevention of obesity. Summary: Four important findings are briefly reviewed: disturbances of sleep and circadian rhythms in children and young adults are risk factors for the development of lifelong obesity; circadian misalignment, as occurs in shift work, has an adverse impact on energy balance and increases the risk of weight gain; the endocannabinoid system, an important regulator of hedonic feeding, could be a potential link between sleep, circadian rhythms, and feeding behavior; and disturbances of the circadian variation in composition of the gut microbiome may be involved in the increased risk of obesity associated with insufficient sleep and circadian misalignment.